MICROWAVE INDUCED PYROLYSIS FOR BIO-OIL PRODUCTION FROM LIGNOCELLULOSIC BIOMASS - Ahmad Afif, Hafizah (2015)
Pyrolysis is one of the technologies that can be utilized to decompose the solid biomass into chemical constituents. The concept of pyrolysis in decomposing solid biomass at high temperature with limited oxygen condition has been prove with a number ofreported studies involving various techniques, settings, and feedstock. Most of the studies, develop the understanding of pyrolysis by conventional heating. Conventional heating of biomass faces issue of heating efficiency since biomass employs relatively high moisture content and low energy density that could slow down the heat transfer process. Inorder to overcome this issue, microwave induced pyrolysis was introduced in this study to decompose biomass into chemical compound. The microwave, heats effectively by delivering energy to material through molecular interaction with electromagnetic field and transfers energy throughout the volume of material. Volumetric heating is the key to reduce the processing time.